Interseismic deformation and strain-partitioning along the Main Köpetdag Fault, Turkmenistan, with Sentinel-1 InSAR time-series. Issue 3 (15th April 2022) - Dodds, N; Daout, S; Walker, R T; Begenjev, G; Bezmenov, Y; Mirzin, R; Parsons, B
SUMMARY: The Main Köpetdag Fault (MKDF) is a predominantly right-lateral strike-slip fault that dissects the northern edge of the Köpetdag mountains of Turkmenistan and Iran. The fault represents the northernmost expression of deformation from the Arabia–Eurasia collision to the east of the Caspian Sea, and plays an important role facilitating the motion of the South Caspian Basin (SCB). Despite the kinematic significance of the MKDF, previous geodetic measurements of the slip-rate across the fault have been highly variable, with a recent geological slip-rate supporting evidence for rapid motion across the fault. To resolve this ambiguity, we derive Sentinel-1 InSAR time-series in both the ascending and descending LOS (line-of-sight) to measure interseismic motion across the MKDF. This implements a processing strategy for the correction and performance analysis of tropospheric models from GACOS (Generic Atmospheric Correction Online Service), which suggests a 25–40 per cent underestimation in the amplitude of the tropospheric path delay in this region. Modelling the rate of fault-parallel motion across the MKDF and combining this with a geological slip-rate constrains 9 ± 2 mm yr –1 right-lateral motion, along with a shallow locking depth of ≈6 km. The LOS time-series resolves path delays of greater than 1 mm yr –1 in both LOS geometries to the north of the MKDF, aligned with mapped frontal thrust scarps to the north of the MKDF. Modelling this as uplift from deformation across these frontal thrusts estimates 4 ± 2 mm yr –1 of shortening across the fault system. This implies that convergence measured with GNSS within the East Caspian Lowlands is partitioned across frontal thrusts to the north of the MKDF. Revising an Iran–Eurasia–SCB velocity triangle suggests that motion along the conjugate MKDF and Shahroud fault zones is representative of the motion of the SCB, which is moving at 10 ± 2 mm yr –1 in a direction of 330° ± 10° relative to Eurasia.